IMPROVING THE TECHNOLOGY OF OBTAINING GRAY SINK ALLOY BRANDED CЧ – 32-52, CЧ – 28-48 USING SECONDARY BLACK METAL FRAGMENTS - Axunjonov Anvarjon Sobirovich; Bektemirov Abdujalol Do‘smuxammad o‘g‘li; Dovulov Shuxrat Bozarovich; Erkinjonov Abdulxamid Baxtiyorjon o‘g‘li (European Science Publishing, 2024)
This article discusses the improved technology of obtaining gray sink alloys branded CЧ – 32-52, CЧ – 28-48, which are the most widely used among sedimentary alloys, using secondary black metal fragments.
Keywords: Secondary black metals, sink alloys, gray brush, graphite, lideburid, CЧ – 32-52, CЧ – 28-48.